SISTEM INFORMASI TRANSAKSI PEMBIAYAAN MURABAHAH PADA BANK BTPN SYARIAH BERBASIS WEB - Eva Sutihat; Agung Sugiarto; Siti Nurlela (International Journal Mathla’ul Anwar of Halal Issues, 2022)
BTPN Syariah Is the 12th Sharia Commercial Bank in Indonesia. In order to get Murabahah Financial Services from BTPN Syariah Saketi Bank, prospective clients need to follow certain steps. Transaction financing at BTPN Syariah Saketi Bank currently still uses manual accounting entry. Customers are demanding transaction data transparency transactions so customers can find out about customer funds coming in and going out at BTPN Syariah Bank. Murabahah Financial Transaction Information System is an information system specially designed or BTPN Syariah Bank to enable financial transactions to be conducted effectively and efficiently. When designing this information system, a structured methodis used, where this method goes through design phases. This computer system uses a MySQL database and has input and output design plans and system implementation plans. Due to the existence of the computer system that organizes data processing tasks for BTPN Syariah Saketi, the other wise designed computer system speeds up the service, which makes the process of applying for grants not take too much time.